Menyoal Pelayanan Publik yang Berkualitas di Era Otonomi Daerah - Malau, Hasbullah (Jurnal Demokrasi, 2009)
The implementation of local autonomy in Indonesia since 2001 has made several changes in governmental paradigm in Indonesia, especially in local government. Nevertheless, the authority delegated from the central to local government has never made any good public service toward the customers or society. This article tries to discuss anything related to implementation of public service during decentralization era in Indonesia, especially in local government. The discussion in this article will include public service reform, public service in the era of local autonomy, models in public service, and equity in public service Kata Kunci: Pelayanan publik, reformasi pelayanan publik, otonomi daerah,